INTEGRASI SMALL GROUP DISCUSSION DAN MINIATURE MATH : EFEKTIVITAS DALAM MENINGKATKAN BERPIKIR KRITIS SISWA - Prasetyo, Anggi Okta; Rizqi, Hesti Yunitiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary mathematics learning still faces difficulties in developing students’ critical thinking because abstract concepts are often presented through routine explanations and exercises. This study examined the use of Small Group Discussion supported by Miniature Math, a three-dimensional city model designed to make cubes and cuboids observable and measurable. A quantitative quasi-experimental study with a nonequivalent control-group design involved 66 fourth-grade students at SD Negeri 2 Kalongan, consisting of 32 students in the experimental class and 34 students in the control class. Participants were selected purposively. Data were collected through eight validated essay items, classroom-observation sheets, student-response questionnaires, and documentation. The test instrument showed high reliability (Cronbach’s alpha = .82). Data were analyzed using Shapiro–Wilk, Levene’s test, an Independent-Samples t Test, descriptive paired statistics, and simple linear regression. The posttest comparison showed a significant difference between the two classes, t(64) = -4.764, p < .001. The experimental-class mean increased from 57.38 to 83.44, while implementation and student-response scores reached 73.17% and 77.73%. The regression output produced R² = .093 and p = .090, indicating a limited and statistically nonsignificant linear contribution that should be interpreted cautiously. The findings support the use of concrete media in structured small-group discussion to strengthen critical-thinking activities, while also emphasizing the need for longer interventions, broader samples, and more precise predictor measurement.